The Impact of Changes in Oral Functioning, Social Support and Spiritual Aspect on The Psychosocial Well-Being Among Oral Cancer Patients in Malaysia: Secondary Data Analysis - Che Musa, Muhd Firdaus; Doss, Jennifer Geraldine; Ghani, Wan Mari Nabillah (2021)
Background: There is growing concern regarding the psychosocial needs among oral cancer patients with restricted oral-functioning due to cancer and its treatment. The current management strategies focus mainly on providing clinical care; with little emphasis given to other aspects of care. Aim: The aim of this research project is to determine the relationship between the changes in oral functioning (OF), social support (SS) and spiritual aspect (SA) with the psychosocial well-being (PSWB) among oral cancer patients in Malaysia. Methods: This is a secondary data analysis on the individual-level HRQoL dataset among cohort patients diagnosed with oral cancer between 2008 till 2015, collected from the Malaysian Oral Cancer Database and Tissue Bank System (MOCDTBS) to examine potential association between HRQoL sub-scales of OF, SS, SA and PSWB across three different visits namely; at baseline (pre-treatment), 1 month; and 3 months-post treatments. Descriptive analysis of HRQoL sub-scales, including correlation and linear regression were undertaken for overall and by the disease-treatment characteristics. This was followed by hierarchical multiple regression analysis in exploring the combined role of SS and SA in explaining the relationship of interest between OF and PSWB. Results: There was a significant deterioration in OF and improvement in PWSB among a cohort group of Malaysian oral cancer patients at their first review visit. At subsequent visits, the PSWB sub-scale continued to demonstrate significant improvement, including the OF and SS sub-scales. In multivariate analyses, SS was the most important predictor for PSWB across all cancer staging or treatment modalities; also mediating the enhancement of OF among the late-stage group at baseline. Nevertheless, SA less likely contributed to OF enhancement except at baseline and second review visit among those treated with combined treatment. Conclusion: The findings provide some insights on how both SS and SA can contribute to improve PSWB among oral cancer patients presenting with compromised oral function. An integrative approach comprising a combination of social and spiritual supportive care with treatment modalities including the repair of oral function could be one model of holistic patient care for oral cancer patients in Malaysia.